Deprivation-specific life tables using multivariable flexible modelling - trends from 2000-2002 to 2010-2012, Portugal - Luís Antunes; Denisa Mendonça; Ana Isabel Ribeiro; Camille Maringe; Bernard Rachet (BMC, 2019)
Abstract Background Completing mortality data by information on possible socioeconomic inequalities in mortality is crucial for policy planning. The aim of this study was to build deprivation-specific life tables using the Portuguese version of the European Deprivation Index (EDI) as a measure of area-level socioeconomic deprivation, and to evaluate mortality trends between the periods 2000-2002 and 2010-2012. Methods Statistics Portugal provided the counts of deaths and population by sex, age group, calendar year and area of residence (parish). A socioeconomic deprivation level was assigned to each parish according to the quintile of their national EDI distribution. Death counts were modelled within the generalised linear model framework as a function of age, deprivation level and calendar period. Mortality Rate Ratios (MRR) were estimated to evaluate variations in mortality between deprivation groups and periods. Results Life expectancy at birth increased from 74.0 and 80.9 years in 2000-2002, for men and women, respectively, and to 77.6 and 83.8 years in 2010-2012. Yet, life expectancy at birth differed by deprivation, with, compared to least deprived population, a deficit of about 2 (men) and 1 (women) years among most deprived in the whole study period. The higher mortality experienced by most deprived groups at birth (in 2010-2012, mortality rate ratios of 1.74 and 1.29 in men and women, respectively) progressively disappeared with increasing age. Conclusions Persistent differences in mortality and life expectancy were observed according to ecological socioeconomic deprivation. These differences were larger among men and mostly marked at birth for both sexes.